Sign, Language, Significance and Communication: Array - Arsith, Mirela; Popa Tanase, Daniela Aurelia (Acta Universitatis Danubius. Communicatio, 2020)
The hypothesis from which we start in our approach is that the sign is also an element of the communication process and non-participant in the signaling process. The constructive character of thought is manifested in language, which is revealed as “the constitutive body of thoughts.” Language, as a reality and a phenomenon characteristic of man, it relates to thinking as language. This is done through the inner form of language. Through speech acts, thinking becomes communicable; the context of communication can be the space of interpretation of the deep relations between thinking and language. What we are pursuing in this paper is to argue that the process of thinking, which assumes concepts, judgments, reasoning, has to do with the meanings. Meaning is an inner property of thought, a relationship: a) between signs; b) between the sign and the object; c) between the people's activity; d) between people who communicate using the signs. Therefore, the significance is multidimensional and belongs to both the sphere of consciousness and any social process.